Human rights, democracy and cultural diversity: living with and among different - Ruiz Vieytez, Eduardo J. (Razón y fe, 2018)
When the need of integration and the always interested «social cohesion» are carried to an extreme, human rights are at risk and they can disappear. What should we do in Europe and in others latitudes when cultural diversity and the diversity of identity of its current populations become a reality to stay? It would be advisable, as the thesis of the author of this article says, «managing diversity» through respecting human rights, through overcoming the idea of assimilationist culture through ourselves and not through nationalization and politization that has always characterized the dominant culture. It is useless to deny the complex cultural reality and the diversity we live and we will live in.
Keywords: Human rights; social cohesion; diversity; «ourselves»; multiculturality; dialogue